Literature Review: Factors Related to the Implementation of School Health Programs (UKS) in Indonesia - Nugrahani, Yuniar Kusuma; Umaroh, Ayu Khoirotul (Tadulako University, 2025)
School Health Program (UKS) are cross-program and sector efforts to improve students' healthy living skills and behaviors in schools. UKS focuses on three main programs, namely health education, health services, and fostering a healthy school environment. The purpose of writing this article is to identify factors related to the implementation of the School Health Program. The method used is a literature review of articles published online with the Google Scholar, Science Directory, and PubMed databases. The selection process uses the PRISMA diagram flow and produces 5 articles for review. The results obtained include several factors related to the implementation of the UKS program, including knowledge, attitudes, human resources, and facilities and infrastructure. The conclusion of this writing is that good knowledge, positive attitudes, competent human resources, and adequate facilities support each other and there needs to be collaboration from all parties, including students, teachers, health workers and local governments that need to be improved to ensure that the UKS program can run effectively and sustainably